A Novel In-House Enzyme-Linked Immunosorbent Assay for Genotype 3 Hepatitis E Virus Reveals High Seroprevalence in Blood Donors in Northern Argentina - Arce, Lorena Paola; Müller, Melisa Florencia; Martinez, Alfredo; Baiker, Armin; Marranzino, Gabriela; Agote, Felicitas; Vizoso-Pinto, Maria Guadalupe (Frontiers in Microbiology, 2019)
Hepatitis E virus (HEV) is an emergent virus that causes acute hepatitis in immunocompetent hosts and chronic hepatitis in immunocompromised ones. In Latin America, the main circulating genotype (GT) is 3, which is usually of zoonotic origin. Diagnosis and seroprevalence studies mainly rely on the detection of specific antibodies. There are scarce data on the seroprevalence of HEV infection in Latin America mainly due to the lack of awareness of HEV circulation. Furthermore, in some countries, like Argentina, HEV testing is not included in routine assays. In order to provide with tools to deepen the knowledge on HEV epidemiology in South America, we designed a new in-house ELISA based on the native recombinant protein ORF2 aa112-608 and demonstrated its potential for detecting anti-HEV IgG in human serum samples. The following conditions were determined: an optimal antigen concentration of 0.25 µg/ml, a serum dilution of 1:80, gelatin as blocking agent, and a secondary antibody dilution of 1:2000. A relative sensitivity of 93.33% (95% confidence interval; 77.93%-99.18%) and a relative specificity of 99.4% (95% confidence interval; 96.71%-99.98%) were determined using a panel of previously characterized sera. When we compared our in-house ELISA with a commercial test (DIA.PRO), we obtained a kappa index of 0.9402 (95% confidence interval, 0.8731-1.0073). We screened 813 blood donor samples with this newly developed ELISA and found a seroprevalence of 9.23% (95% confidence interval, 7.33-11.43%). We show for the first time evidence of past HEV infection in Tucuman, the most populated city in northern Argentina. We expect that this study will raise the interest of health decision makers, who should intercede to include indirect testing of HEV in regular diagnostic protocols. In conclusion, the in-house ELISA developed in this work demonstrated a high sensitivity and specificity comparable to those of an already licensed commercial IgG ELISA, which can be used as an epidemiologic tool for HEV surveillance.